MEASURING LEVEL OF EDUCATIONAL MANAGEMENT IN MANAGING A BOXING LESSON AMONG SECOND-YEAR STUDENTS AT COLLEGE OF EDUCATION AND SPORTS SCIENCES, UNIVERSITY OF BASRA, FROM STUDENTS' PERSPECTIVE - Fouad Abdul Mahdi Mahmoud Al-Hamdani; Suhail Mishari Hamid Darwish (Journal Olahraga Rekat (Rekreasi Masyarakat), 2025)
Background. Developing a lesson management scale for students in the College of Physical Education and Sports Sciences (second year), in the boxing course. Objectives. This study aims to identify the most important axes of learning management variables for students of the Faculty of Physical Education and Sports Science (second year) in boxing courses. It also aims to develop an education management scale at the Faculty of Physical Education and Sports Science. Method. The research method is based on the main and main matters to obtain accurate data for analysis and its links to the analysis of the research problem. A number of researchers have discovered the descriptive nature of the survey and the research problem, mentioning the studies and descriptive contributions in adding contemporary and real information about an existing situation and a condition or problem of a specific phenomenon, whether sports or educational, which created a positive effect in the new variable, and this has obtained approvals and support and the latest new technologies for development towards the better. Results. The majority of administrations responsible for the educational process believe that the educational process is the sole responsibility of the subject teacher and that he is the main axis around which the teaching and learning process and the educational process as a whole revolves. This belief is not without error, as the subject teacher is an important, effective and highly influential axis, but there are other factors that complement his work, such as the student, the administration, the curriculum, the means and methods of education, as they all work side by side to make the educational process successful and achieve the desired goals of this process. Conclusion. Role and importance of education, represented by the senior management of the educational institution, becomes clear to us in providing a collection of tools, means, and places for the success of the lesson, along with what is provided by the professor concerned with the lesson. Here, the researcher addressed the boxing lesson for the second stage, as he is a teacher of this academic subject, and that this academic subject needs important tools and means for its success and conveying the scientific material to the student.